2011
DOI: 10.1007/s00234-011-0946-z
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-weighted MR imaging in persistent hemiplegic migraine

Abstract: PWI should be indicated for patients with migraine attacks accompanied by auras to assess the sequential changes in cerebral perfusion and to better understand its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…Subtle perfusion abnormalities in migraine patients are well recognised, with reduced CBF the most commonly described 20–22. One recent report suggested that TTP asymmetry was the most sensitive parameter23 and matches our experience. It would appear that the frequency of abnormalities (1/23 in our series) is quite low, but this may relate to timing as the majority of reports relate to the aura phase.…”
Section: Discussionsupporting
confidence: 90%
“…Subtle perfusion abnormalities in migraine patients are well recognised, with reduced CBF the most commonly described 20–22. One recent report suggested that TTP asymmetry was the most sensitive parameter23 and matches our experience. It would appear that the frequency of abnormalities (1/23 in our series) is quite low, but this may relate to timing as the majority of reports relate to the aura phase.…”
Section: Discussionsupporting
confidence: 90%
“…Studies employing PWI or SPECT to investigate hemodynamic changes during acute attacks or soon thereafter showed hypoperfusion or hyperperfusion of cerebral hemispheres that resolved spontaneously after the attacks without permanent sequelae or signs of cerebral ischemia on follow up. 28,29 Proton MR spectroscopy (MRS) showed decreased N-acetylaspartate/creatine ratio in the corresponding hemisphere. Overall, these multimodal imaging data support a primary neuronal dysfunction in FHM.…”
Section: This Review Was Initiated With a Pubmed Search Of The Us Natmentioning
confidence: 99%
“…Fedak et al reported four pediatric cases of SHM where these flow abnormalities spontaneously resolved within 24 h after hospital presentation [23]. Other authors have reported similar findings [24][25][26]. Sugrue et al described a case wherein evidence of cerebral edema without evidence of infarction was documented in a patient with persistent hemiplegia following headache [27].…”
Section: Sporadic Hemiplegic Migrainementioning
confidence: 71%